(Invited) A Path Toward Vertical GaN Superjunction Devices. (8th September 2020) - Khachariya, Dolar; Szymanski, Dennis; Reddy, Pramod; Kohn, Erhard; Sitar, Zlatko; Collazo, Ramon; Pavlidis, Spyridon
Abstract : GaN devices offer exciting competition to incumbent technologies to meet the growing demand for high power electronic devices. The wide bandgap of GaN makes it possible to achieve higher breakdown voltages and reduced on-resistances compared to traditional Si in unipolar devices, as predicted by the classical Baliga figure of merit (BFOM). However, unipolar performance limits can be circumvented using the superjunction (SJ), which has been demonstrated experimentally in both Si and SiC. Due to the current difficulties with selective area doping in GaN, experimental reports of vertical GaN SJs are lacking. In response, we propose the use of the lateral polar junction (LPJ), which is unique to III-Nitrides, to create next-generation vertical GaN SJ devices. We develop a model that provides first order design equations for such a device, and validate it using TCAD simulations of a 1.2 kV diode. A proposed manufacturing approach for LPJ-based GaN SJ is provided.